RF powered ZigBee 3.0 IoT System - Zhang, Boyan (Nanyang Technological University, 2022)
In the traditional Internet of Things (IoT) systems, most of them use battery or AC power to DC power (AC-DC) supply, and the above two power supply methods do not cause too much trouble for areas such as homes and shopping malls. However, the use of battery power or AC-DC is not very realistic when it comes to the large-scale use of IoT devices, such as large factories and unmanned areas in the field. The former is time-consuming and laborious due to the large number and wide area when replacing batteries, while the latter is too demanding for the hardware of the site, requiring the provision of AC power outlets near each device, while wired power supply may have the risk of aging wires causing a short circuit and other risks. In order to solve the problem of difficult sensor power supply in a large area, this dissertation compared the existing mainstream IoT devices in the market, realize the normal operation of IoT devices with lower power consumption through relevant algorithms and hardware circuit design, and design an RF energy-based ZigBee sensor network system by combining RF energy-powered system with low-power IoT system. After testing, when the voltage is set to 4.2V, the RF energy harvester can provide a maximum current of 2mA without an external supercapacitor and a maximum current of 12mA with an external supercapacitor. At an operating voltage of 3.3V, the standby current of the ZigBee is only about 1.3μA, and when sending data at the default power, the current is about 10mA for a duration of 30ms.